Review of taxonomic status of Polypedilum quinquesetosum (Edwards, 1931) (Diptera, Chironomidae) - Fuentes, María Cecilia (2014)
The taxonomic status of Polypedilum quinquesetosum (Edwards) is reviewed upon the study of the male holotype of the species and new findings. After the character analysis, this species belongs to the subgenus Tripodura Townes and the new combination is established. The species diagnosis is expanded, the relationships with the rest of the Neotropical species of the subgenus are discussed and its geographical distribution is extended.